2002
DOI: 10.1093/deafed/7.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Social Processes and Outcomes of In-School Contact Between Deaf and Hearing Peers

Abstract: Studies of social processes and outcomes of the placement of deaf students with hearing peers cannot be easily summarized, but can be grouped into a least four major categories of focus: social skills, interaction and participation, sociometric status and acceptance, and affective functioning. We review 33 studies available since 1980 in which a mainstreamed or included deaf sample was compared to another group. Studies indicated (1) that hearing students were more socially mature than deaf students in public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 28 publications
4
42
1
3
Order By: Relevance
“…• In a review of 33 studies published after 1980, Kluwin, Stinson, and Colarossi (2002) identified four main areas of concern for children with hearing loss when compared with hearing peers, including social skills, interaction/participation, sociometric status/acceptance, and affective functioning.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…• In a review of 33 studies published after 1980, Kluwin, Stinson, and Colarossi (2002) identified four main areas of concern for children with hearing loss when compared with hearing peers, including social skills, interaction/participation, sociometric status/acceptance, and affective functioning.…”
Section: The Problemmentioning
confidence: 99%
“…The studies published on self-esteem and social competence have generally evaluated older school children and adolescents and have spanned a variety of methodologies (Kluwin, 1993;Kluwin et al, 2002). Taken together they suggest that mainstreamed deaf students may not have fully successful relationships with hearing peers, but that specific interventions may improve social outcomes.…”
Section: The Social Consequences Of Inclusionmentioning
confidence: 99%
“…пол, контакт) са ставовима према овој групи људи. Страна истраживања (Margalit & Marion, 1983;Furham & Lane, 1984;Kluwin at al, 2002;Cambr, 2002;Nikolaraizi at al, 2005), углавном дају налазе о прихватајућим ставовима према особама са сметњама у развоју, мада, критичка дискусија резултата не говори увек о недвосмисленом прихватању. Анализа иностране и наше истраживачке праксе указује на тешкоће у процени ставова према особама са сметњама у раз-воју с обзиром да су налази често неконзистентни, а у једном делу истраживања и контрадикторни (Димоски, 2010: 400).…”
Section: социјални ставови према особама са сметњама у развојуunclassified
“…They conclude that promoting participation is an important first step towards social integration, and frequent and mutually enjoyable participation may provide a foundation for true acceptance. Kluwin et al (2002) found that the greater the contact the students had with each other, the more the participation of D/HH students in social activities with hearing peers. The majority of the reviewed studies reported that hearing peers accepted deaf students in classes, although factors such as extent of contact and gender may have an effect.…”
Section: Introductionmentioning
confidence: 98%
“…8(2): 62-74 (2006) Published online in Wiley InterScience (www.interscience.wiley.com) DOI: 10.1002/dei.190 A review of the literature indicates that most, but not all, studies support the positive aspects of inclusion mentioned above. That is, studies have reported satisfactory outcomes for academic progress and social development of D/HH students, including positive attitudes toward and acceptance of D/HH students by their hearing peers (Kluwin, 1999;Kluwin and Stinson, 1993;Kluwin et al, 2002;Luckner, 1999;Power and Hyde, 2002;Powers, 1996). On the other hand, a few studies have reported that D/HH students have encountered negative attitudes held by their hearing peers, have experienced isolation, or loneliness, or have failed to establish close relationships with their hearing peers (e.g.…”
Section: Introductionmentioning
confidence: 99%